Correlation Between Sonic and Mechanical Test Results on Stone Masonry Walls - Rachel Martini (2019)
Heritage constructions are the inheritance of the society and must be preserved because of their historical and cultural value. To preserve and rehabilitate these structures, an extensive knowledge of its mechanical properties is required. To obtain this information priority should be given to the use of non-destructive techniques. In this work, it is proposed to use the correlation of sonic and mechanical tests, performed in seven double-leaf stone masonry walls constructed in the laboratory. Four types of two leaves masonry walls were constructed, with variations in its structural configuration. Based on uniaxial compression tests performed on these stone masonry walls, mechanical properties were obtained. These data were correlated with sonic test results. Two sonic test sequences were performed. In the first sequence, direct and indirect tests were performed before and after the damaging mechanical compression tests. For the second sequence of sonic tests, direct and indirect tests were implemented at each loading level during the compression test, for which fewer acquisition points were defined, to avoid loading redistribution and relaxation during the sonic data acquisition. Several difficulties were encountered in this process. Despite these difficulties, both used tests presented coherent and correlated results. For the sonic tests, as expected, the higher wave velocity locations are those from the direct test across the walls header blocks. With the sonic tests performed during the compression tests, it was possible to monitor the varying sonic behavior of the walls, and the accuracy of the sonic test results when compared with the compression test results. (c) 2019, RILEM.